1998
DOI: 10.1074/jbc.273.30.19228
|View full text |Cite
|
Sign up to set email alerts
|

Some, but Not All, Glycine Substitution Mutations inCOL7A1 Result in Intracellular Accumulation of Collagen VII, Loss of Anchoring Fibrils, and Skin Blistering

Abstract: COL7A1 gene mutations cause dystrophic epidermolysis bullosa, a skin blistering disorder. The phenotypes result from defects of collagen VII, the major component of the anchoring fibrils at the dermo-epidermal junction; however, the molecular mechanisms underlying the phenotypes remain elusive. We investigated naturally occurring COL7A1 mutations and showed that some, but not all, glycine substitutions in collagen VII interfered with biosynthesis of the protein in a dominant-negative manner. Three point mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 36 publications
3
63
1
Order By: Relevance
“…Consistent with this notion, our studies demonstrated that this mutation, similar to R2063W, also leads to destabilization of the triple helix and makes the mutant C7 more susceptible to protease digestion. It is interesting to note that four other C7 mutations, G2006D, G2034R, G2015E, and R2008G, within exon 73 next to the hinge region have also been shown to interfere with protein folding in a dominant negative manner and cause intracellular accumulation of the mutant molecules (15,40). However, we did not detect any difference in the secretion of these two mutant proteins when compared with wild type C7.…”
Section: Figure 9 Migration Of Human Keratinocytes On Various C7 Mutcontrasting
confidence: 44%
“…Consistent with this notion, our studies demonstrated that this mutation, similar to R2063W, also leads to destabilization of the triple helix and makes the mutant C7 more susceptible to protease digestion. It is interesting to note that four other C7 mutations, G2006D, G2034R, G2015E, and R2008G, within exon 73 next to the hinge region have also been shown to interfere with protein folding in a dominant negative manner and cause intracellular accumulation of the mutant molecules (15,40). However, we did not detect any difference in the secretion of these two mutant proteins when compared with wild type C7.…”
Section: Figure 9 Migration Of Human Keratinocytes On Various C7 Mutcontrasting
confidence: 44%
“…60 It has been postulated that some glycine substitution mutations interfere with the formation of the stable triple helix of type VII collagen, preventing their secretion into the extracellular space, and thus leading to the intracellular accumulation of type VII collagen. 61 …”
Section: Consequences Of Splice-junction Mutationsmentioning
confidence: 52%
“…Unlike many other glycine substitution mutations in the genes for skin basement membrane collagens (20,21,40), the mutation G627V causes a drastic reduction of the conformational stability of the Col15 domain. The mutated fragment was partially digested by trypsin already at 4°C and completely abolished at 16°C.…”
Section: Discussionmentioning
confidence: 99%